1987
DOI: 10.1017/s0021859600079387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen and phosphorus on the production potential of pearl millet–cow pea or green gram intercropping systems under rainfed conditions

Abstract: SummaryResults are described of an experiment involving various pearl millet–cow pea or green gram planting and interplanting systems under four levels of nitrogen and two levels of phosphorus. Planting of pearl millet in paired rows of 30 and 70 cm gave as much yield as normal planting in uniform rows of 50 cm. The productivity per unit area was increased considerably when pearl millet was interplanted with one row of cow pea or green gram. Cow pea gave higher yield than green gram. Nitrogen fertilizer increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 2 publications
2
6
0
Order By: Relevance
“…The increase may be attributed to increase in vegetative cover due to application of fertilizer, while ultimately enhanced straw. Similar results have been reported by Kaushik and Gautam (1987) and Singh et al (1975). Table 4: Effect of nitrogen application on straw and grain yield of legumes and maize (kg haG 1 ) Means with different letters in a row are statistically significant at alpha = 0.05; N o = Control; N 1 = 100 kg haG 1 ; N o = Non-significant The grain yield data indicated that there was not significant variation in the yield of soybean and mash with and without fertilizer application, however, there was significant increase in the yield of maize crop indicating that the legumes meet their need of nitrogen by utilizing the biological nitrogen.…”
Section: Straw and Grain Yieldsupporting
confidence: 92%
See 1 more Smart Citation
“…The increase may be attributed to increase in vegetative cover due to application of fertilizer, while ultimately enhanced straw. Similar results have been reported by Kaushik and Gautam (1987) and Singh et al (1975). Table 4: Effect of nitrogen application on straw and grain yield of legumes and maize (kg haG 1 ) Means with different letters in a row are statistically significant at alpha = 0.05; N o = Control; N 1 = 100 kg haG 1 ; N o = Non-significant The grain yield data indicated that there was not significant variation in the yield of soybean and mash with and without fertilizer application, however, there was significant increase in the yield of maize crop indicating that the legumes meet their need of nitrogen by utilizing the biological nitrogen.…”
Section: Straw and Grain Yieldsupporting
confidence: 92%
“…Table 4: Effect of nitrogen application on straw and grain yield of legumes and maize (kg haG 1 ) Means with different letters in a row are statistically significant at alpha = 0.05; N o = Control; N 1 = 100 kg haG 1 ; N o = Non-significant The grain yield data indicated that there was not significant variation in the yield of soybean and mash with and without fertilizer application, however, there was significant increase in the yield of maize crop indicating that the legumes meet their need of nitrogen by utilizing the biological nitrogen. These results are in accordance with that of Kaushik and Gautam (1987) who revealed that cowpeas and green gram produced highest yield at 30 kg N haG 1 and further increment of nitrogen fertilizer did not cause marked improvement in the yield.…”
Section: Straw and Grain Yieldsupporting
confidence: 92%
“…Phosphorus fertilizer application at 40kg P205/ ha increased intercrop grain yield as compared to sole crop pearl millet (Kaushik and Gautam, 1987). The response to P was observed only on soils initially low in P.…”
Section: Phosphorusmentioning
confidence: 90%
“…In low and unpredictable rainfall areas where irrigation is unavailable, early maturing and/or water stress-tolerant legumes and small-grained cereals are cultivated. Examples are finger millet and green gram in India (Kaushik and Gautam, 1987), oats and vetch in Cyprus (Droushiotis, 1989), cowpea and sorghum in the sub-Saharan West African subregion (Ntare, 1989). In seasons or areas where rainfall is abundant, maize and rice are often planted with such legumes as field bean, cowpea and soybean (Ezumah et al, 1987).…”
Section: Common Mixed-cropping Systemsmentioning
confidence: 99%
“…These results were supported by the findings of Samui et al (1979), Reddy et al (1986), Abdulsalam and Subramaniam (1988), Purushotham et al (1988), Raju et al (1990), Dubey et al (1991) Panda et al (1999) and Bindra et al (2000). Many researchers also reported that cereal component in legumes based intercropping yielded more at higher levels of nitrogen application (Reddy et al 1980;Ramesh and Surve 1984;Ofori and Stern 1986;Ezumah et al 1987;Rao et al 1987;Kaushik and Gautam 1987;Chowdhury and Rosario 1992;Rafey and Prasad 1992;Bhagat and Dhar 1995;Kushwaha and Chandel 1997;Mandal et al 2000;Sarwagi and Tripathi 1999;Shivay et al 1999;Shivay and Singh 2000;Singh, 2006b). Whereas, same were failed to show its effect on pigeonpea (Table 3 and 4).…”
Section: Growth Yields and Pigeonpea Grain Equivalent Yieldmentioning
confidence: 99%